2020
DOI: 10.1177/1932296820964264
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in Critically Ill Patients With COVID-19: Results of an Emergent Pilot Study

Abstract: Background: Amidst the coronavirus disease 2019 (COVID-19) pandemic, continuous glucose monitoring (CGM) has emerged as an alternative for inpatient point-of-care blood glucose (POC-BG) monitoring. We performed a feasibility pilot study using CGM in critically ill patients with COVID-19 in the intensive care unit (ICU). Methods: Single-center, retrospective study of glucose monitoring in critically ill patients with COVID-19 on insulin therapy using Medtronic Guardian Connect and Dexcom G6 CGM systems. Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 30 publications
(44 reference statements)
2
53
0
2
Order By: Relevance
“…Another developing application of rtCGM relevant to both T1D and T2D is use in the inpatient setting, where frequent monitoring with remote display may show significant advantages in nursing demands, more dynamic therapeutic adjustments, and reduced hypoglycemia [63][64][65][66][67] . This use requires further research, including cost-benefit analysis, but holds great promise.…”
Section: G Other Considerations and Future Directionsmentioning
confidence: 99%
“…Another developing application of rtCGM relevant to both T1D and T2D is use in the inpatient setting, where frequent monitoring with remote display may show significant advantages in nursing demands, more dynamic therapeutic adjustments, and reduced hypoglycemia [63][64][65][66][67] . This use requires further research, including cost-benefit analysis, but holds great promise.…”
Section: G Other Considerations and Future Directionsmentioning
confidence: 99%
“…For the full cohort, there was a 14% decrease (235.7 to 202.7 mg/dL, P =0.0003) in mean sensor glucose. Sadhu et al [ 29 ] reported similar accuracy between the Medtronic Guardian Connect (Medtronic Minimed, Northridge, CA, USA) and Dexcom G6 devices in a cohort of 11 ICU patients. This ICU data is promising for eventual routine use of CGMs in an ICU setting.…”
Section: Who Is a Candidate For Using A Cgm In The Intensive Care Unitmentioning
confidence: 94%
“…[28][29][30][31][32][33][34] Continued innovations are planned, including: (1) decreased physical footprint of these devices, (2) reduction or elimination of calibrations, (3) assessment of the devices in broader populations with alternate sites of insertion, and (4) the insertion devices for many devices will be made easier to use. Finally, with the COVID-19 pandemic, the FDA will not object to the application of certain sensors in hospitalized persons with diabetes given the extraordinary circumstances, 35,36 and use of these devices has now been shown to be feasible in the inpatient setting. 37 Furthermore, use of CGM based metrics has helped guide optimization of therapy during telehealth encounters.…”
Section: Clinical Uses Of Artificial Intelligencementioning
confidence: 99%
“…145 Unexpectedly, the COVID-19 pandemic presented and, in response, the FDA produced a statement of "no objection" for the inpatient use of CGM during the COVID-19 crisis. 36,146 Hence, CGM systems were being used "off label" to help reduce exposure and preserve personal protection equipment. These new guidelines offer recommendations on the potential use of CGM and AID systems for hospitalized patients taking under consideration the existence of evidence to support its safe use.…”
Section: The Dts Guideline For Continuous Glucose Monitors and Automated Insulin Dosing Systems In The Hospitalmentioning
confidence: 99%